The theoretical study on electronic structure and electromagnetic properties of α-MnO2 based on crystal defects. Issue 3 (4th December 2014) - Duan, Yuping; Chen, Junlei; Zhang, Yahong; Wang, Tongmin
Abstract : First-principles calculations based on density functional theory (DFT) have been carried out to investigate the effects of crystal defects (intrinsic vacancy defects and ion doping) on the microwave dielectric response and the correlative electromagnetic properties of α -MnO2 systematically. The possible role of crystal defects in electromagnetic performance is studied utilizing density of states (DOS) and the bond length between the manganese and oxygen. Lattice distortion is induced by the introduction of crystal defects. The spin-electronic DOS demonstrates that Ni doping enhances the spin-polarization of MnO2, which indicates that the Ni-doped MnO2 possesses certain magnetic characteristic, which is helpful for magnetic loss. The emergence of a new defect mode, contributes to the relaxation polarization phenomenon, so as to enhance the dielectric loss ability. In addition, through the change of the bond length and pseudo gap width, it can be learned that the bond strength and covalency of Mn-O bonds are weakened, which increases the dielectric loss of MnO2 . The results throw light on the exploration of theoretical research on the microwave absorbing properties of MnO2 with crystal defects.